Antimicrobial resistance characteristics of multidrug resistance and extended-spectrum beta-lactamase producing Escherichia coli from several dairy farms in Probolinggo, Indonesia - AGUS WIDODO; MIRNI LAMID; MUSTOFA HELMI EFFENDI; ASWIN RAFIF KHAILRULLAH; SHENDY CANADYA KURNIAWAN; OTTO SAHAT MARTUA SILAEN; KATTY HENDRIANA PRISCILIA RIWU; LITA RAKHMA YUSTINASARI; DANIAH ASHRI AFNANI; FIDI NUR AINI EKA PUJI DAMEANTI; SANCAKA CHASYER RAMANDINIANTO (Society for Indonesian Biodiversity, 2023)
Abstract. Widodo A, Lamid M, Effendi MH, Khairullah AR, Kurniawan SC, Silaen OSM, Riwu KHP, Yustinasari LR, Afnani DA, Dameanti FNAEP, Ramandinianto SC. 2022. Antimicrobial resistance characteristics of multidrug resistance and extended spectrum beta-lactamase producing Escherichia coli from several dairy farms in Probolinggo, Indonesia. Biodiversitas 23: 215-221. Escherichia coli bacteria initially reside in the digestive tract of humans and animals but are able to adapt to new environments that are different from their initial habitat. The pathogenicity of E. coli can occur when these bacteria grow more than normal limits, produce toxins, and are resistant to certain types of antibiotics. The purpose of this study was to investigate the antimicrobial resistance characteristics of MDR and ESBL-producing E. coli from several dairy farms in the Probolinggo district of East Java province, Indonesia. A total of 150 samples consisting of 109 milk and 41 environmental samples from 41 dairy farms were used for isolation. TSIA and IMViC biochemical tests were used to identify E. coli bacteria. Escherichia coli resistance profile was obtained through disc diffusion test on several antibiotics, namely tetracycline, streptomycin, trimethoprim, chloramphenicol and aztreonam. Escherichia coli that was resistant to 3 or more antibiotics was defined as MDR. The results of isolation and identification obtained 124 (82.6%) isolates characterizing E. coli bacteria. The antimicrobial susceptibility test of E. coli showed 9 (7.26%) MDR isolates and 2 (22.22%) ESBL isolates by double-disc synergy test (DDST). MDR E. coli was dominated by the pattern of antimicrobial drug resistance TE-S-W (tetracycline, streptomycin, trimethoprim) with a total of 8 (38.10%) isolates, followed by antimicrobial drug resistance pattern TE-S-W-ATM (tetracycline, streptomycin, trimethoprim, aztreonam) with one (4.76%) E. coli isolates. The pattern of antimicrobial drugs of ESBL E. coli showed in one (11.11%) sample of ESBL E. coli from a milk sample with the pattern of TE-S-W-ATM (tetracycline, streptomycin, trimethoprim, aztreonam) and one (11.11%) sample ESBL E. coli (AL 30) from the environmental sample with a pattern of TE-S-W pattern (tetracycline, streptomycin, trimethoprim). The discovery of MDR E. coli isolates and ESBL E. coli from milk and environmental samples at several dairy farms in Probolinggo district, East Java, Indonesia is a matter of concern and requires real action to reduce antibiotic resistance.